The Effect of Compensation, Motivation and Work Discipline on Employee Performance at PT Totoku Toryo Indonesia - Muhamad Natsir; sonny hersona; Dede Jajang Suyaman (Institute of Computer Science (IOCS), 2022)
This study aimed to analyze the effect of compensation, motivation and work discipline on employee performance at PT Totoku Toryo Indonesia. The data used in this study were primary data that obtained through questionnaires to employees of PT Totoku Toryo Indonesia. The population in this study was 98 employees at PT Totoku Toryo Indonesia. Determination of samples using population studies. data analysis using multiple linear regression analysis. Based on the results of testing the hypothesis it can be stated that compensation affects the performance of employees at PT Totoku Toryo Indonesia or H1 accepted. Motivation affects the performance of employees at PT Totoku Toryo Indonesia or H2 received. Work discipline affects the performance of employees at PT Totoku Toryo Indonesia or H3.